Aplicação da reação em cadeia da polimerase (PCR) e amplificação aleatória de DNA polimórfico (RAPD-PCR) na detecção e identificação de Leptospira sp - Isabela Farnezi Veloso (1999)
Leptospirosis is a disease economically important because it is one of the main infectious diseases that affect many animal species. In order to detect Leptospira sp by PCR analysis using the pair of primers Lep13/Lep14, three DNA extraction methods were used, All seven strains treated with proteinase K were PCR positive. All four strains treated with plant proteinase (E6870) were PCR positive, Only two strains were PCR positive when DNA from hve strains were extracted by heating. Sequential dilutions of L, hardjo/Hardjoprajitno (CTG) in urine were subjected to PCR with primers Lep13/Lep14 and its detection limit was 10²cels/mL. RAPD-PCR with primers B11/B12 was used to differentiate between bratislava, tarassovi, pomona, szwajizak, hardjo/Hardjoprajitno (OMS), hardjo/Hardjoprajitno (CTG) and mini serovars and as well as to characterize sequential dilutions of, hardjo/Hardjoprajitno (CTG) in urine. The tirst produced different and charactenstic band pattems for each strain tested. In the last, the detection limit was 10 4cells/mL. These results show that PCR can be used in detection of Leptospira sp in urine and that RAPD-PCR can be used in identihcation, characterization and differentiation of serovars.